2018
DOI: 10.1002/ccd.27520
|View full text |Cite
|
Sign up to set email alerts
|

Association of stent‐induced changes in coronary geometry with late stent failure: Insights from three‐dimensional quantitative coronary angiographic analysis

Abstract: Our study suggests that a change in the natural tortuous course of the coronaries by stent implantation with the decrease in coronary bending angle is a potentially major contributor in stent failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(50 reference statements)
0
2
0
1
Order By: Relevance
“…Помимо моментального влияния стента, большой интерес представляют отложенные гемодинамические изменения. Так, в работе [22] авторы исследовали влияние угла изгиба при поражениях коронарных артерий на проходимость стента в отдаленном периоде. Анализ показал, что изменение естественного извилистого хода коронарных сосудов при имплантации стента с уменьшением угла изгиба коронарных артерий является потенциально основным фактором, способствующим несостоятельности стентированного сегмента.…”
Section: Discussionunclassified
“…Помимо моментального влияния стента, большой интерес представляют отложенные гемодинамические изменения. Так, в работе [22] авторы исследовали влияние угла изгиба при поражениях коронарных артерий на проходимость стента в отдаленном периоде. Анализ показал, что изменение естественного извилистого хода коронарных сосудов при имплантации стента с уменьшением угла изгиба коронарных артерий является потенциально основным фактором, способствующим несостоятельности стентированного сегмента.…”
Section: Discussionunclassified
“…The authors described coronary curvatures by measuring the maximum and mean bending angles at different time points. They showed that the mean systolic post-stent bending angle and the change in the mean systolic bending angle after stenting may be predictors of restenosis [17]. In that study the maximum and mean bending angles were chosen to describe the target segment’s bending angles.…”
Section: Discussionmentioning
confidence: 99%
“…Once implanted, coronary stents will be exposed to cyclic deformation at least 86,400 times per day. Therefore, the indices of dynamic arterial morphology may be useful to estimate stent failure risk (35)(36)(37). For example, Girasis et al (36,37) analyzed the dynamic changes in 3D bifurcation angle (BA) of the left main coronary artery.…”
Section: Assessment Of the Mechanical Failure Risk Of Coronary Stentsmentioning
confidence: 99%